(3cJGH aj GdWHs - (3GHf GdHWQjb , jhMfG Hf GdHWQjb,J (B200 (3g` s
(3ChdgG (B:s
(3PcQ GdMeGA Cf GdcO hPGJ GdeCehQ GdCYVGA GdQFjSjI JfbSe ai SjQgG Edi bSejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B210 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs